Ice-Breaking Activities and Student Learning Interest in Economics Classrooms: Evidence from Secondary Education - Nur Eti; Muhammad Yany; Sandi (Yayasan Ahmar Cendekia Indonesia, 2026)
Learning interest is one of the key factors influencing the effectiveness of the learning process. Low learning interest may reduce students' attention, participation, and engagement in classroom activities, particularly in Economics learning. One instructional strategy that can be implemented to address this issue is ice breaking, which aims to create a more enjoyable learning environment, improve students' concentration, and enhance their enthusiasm during the learning process. This study aimed to analyze the effectiveness of implementing ice breaking in improving students' learning interest in Economics at SMAN 14 Bone. The study employed a quantitative approach using an ex post facto research design. The population consisted of 259 tenth-grade students, while the sample comprised 32 students from Class X.5 selected through purposive sampling. Data were collected using observation, documentation, and questionnaires that had met the validity and reliability requirements. The data were analyzed using descriptive statistics through frequency distribution and percentage analysis. The findings revealed that the implementation of ice breaking was categorized as high to very high across all measured indicators, while students' learning interest ranged from moderate to very high. These findings indicate that the implementation of ice breaking is effective in creating a more conducive learning environment, enhancing students' enthusiasm, maintaining their concentration, and fostering their learning interest. Therefore, ice breaking can serve as an alternative instructional strategy for teachers to improve the quality of Economics learning.